Autenticita a představy v antropologii turismu - Půtová, Barbora (Lidé města, 2018)
The anthropology of tourism represents a relatively new and dynamically developing sub-discipline and thematic field of sociocultural anthropology. The pivotal research topics of the anthropology of tourism are authenticity and tourism imaginaries. The main objective of this paper is the theoretical analysis of particular approaches to the studies of authenticity as they have been developed since the 1970s. Special attention is paid to the phenomenon of tourism imaginaries, which have been the subject of the anthropology of tourism since the 1990s. Therefore, this paper includes the typologies of these categories, as well as further elaboration of the category of the tourists’ perspective, including how theory makes this perspective more accurate and gradually differentiated. This paper presents the development of research terms and categories in the wider context of the development of the anthropology of tourism, and analyses the power relations that affect the relations between guests and hosts.